The Effect of Gender Diversity on Company Performance: Study of Companies Listed on the IDX - Sofiana, Agus; Achmad Fauzi; Tiong Lie Budi Haryono T; Zarra Noor Jannah; Evaristus Lopis (Dinasti Publisher, 2024)
Gender diversity/Board Gender Diversity (BGD) as an issue in human resource management. This research reviews the impact of gender diversity on the performance of companies listed on the Indonesia Stock Exchange (IDX) in 2023. The study uses qualitative research methods with literature study or the Systematic Literature Review (SLR) research type. More than 40 % of companies listed on the IDX have not implemented gender representation on the board of directors. Study selected articles by identifying and reviewing topic suitability. The results of the analysis of the condition of manufacturing companies, showed that Board Gender Diversity (BGD) can improve company performance. Meanwhile, in several other companies, BGD can reduce company performance